Development Status and Trend of U.S. Equipment for Underwater Special Operations - Zhiwei ZHANG; Zejiang FANG; Runmin HE; Qi ZHAO; Zhaotong ZHU (水下无人系统学报, 2024)
In recent years, as the western countries led by the United States have shifted their strategic focus from ocean to offshore, offshore shallow waters have become the focus of attack and defense for countries. With the distributed combat background of manned and unmanned cooperation, underwater special operation platforms have begun to play an increasingly important role. This article was based on the latest national defense research and procurement budget for the US fiscal year 2024 and focused on the development status and research trends of equipment for underwater special operations such as swimmer delivery vehicle(SDV), dry combat submersible(DCS), dry deck shelter(DDS), combat diving (CBDIV), undersea craft mission equipment(UCME), and small undersea unmanned vehicle(SUUV)in underwater system projects, so as to provide useful references for future research on underwater special equipment.